Long-term cost-effectiveness of quality of diabetes care: Experiences from private and public diabetes centers in Iran - Rahill Sadat Shahtaheri; Yahya Bayazidi; Majid Davari; Abbas Kebriaeezadeh; Sepideh Yousef; Alireza Mahdavi Hezaveh; Abolfazl Sadeghi; Ahmed Hayder Mohsin Al Lami; Hadi Abbasian (Health Economics Review, 2022)
Background: The quality of health care has a signifcant impact on both patients and the health system in terms of long-term costs and health consequences. This study focuses on determining the long-term cost-efectiveness in quality of diabetes care in two diferent settings (private/public) using longitudinal patient-level data in Iran. Methods: By extracting patients intermediate biomedical markers in under-treatment type 2 diabetes patients(T2DP) in a longitudinal retrospective study and by applying the localized UKPDS diabetes model, lifetime health outcomes including life expectancy, quality-adjusted Life expectancy (QALE) and direct medical costs of managing disease and related complications from a healthcare system perspective was predicted. Costs and utility decrements had derived on under-treatment T2DP from 7 private and 8 Public diabetes centers. We applied two steps sampling mehods to recruit the needed sample size (cluster and random sampling). To cope with frst and secondorder uncertainty, we used Monte-Carlo simulation and bootstrapping techniques. Both cost and utility variables were discounted by 3% in the base model. Results: In a 20-year time horizon, according to over 5 years of quality of care data, outcomes-driven in the private sector will be more efective and more costly (5.17 vs. 4.95 QALE and 15,385 vs. 8092). The incremental cost-efectiveness ratio (ICER) was 33,148.02 per QALE gained, which was higher than the national threshold. Conclusion: Although quality of care in private diabetes centers resulted in a slight increase in the life expectancy in T2DM patients, it is associated with unfavorable costs, too. Private-sector in management of T2DM patients, compared with public (governmental) diabetic Centers, is unlikely to be cost-efective in Iran.
Keywords: 330; Type 2 diabetes mellitus; Localized UKPDS model; Private sector; Public sector; Cost-efectiveness analysis; Quality of care; Iran